Metaphor and Metonymy in Ancient Dream Interpretation: The Case of Islamic-Iranian Culture - Rahman Veisi Hasar (Journal of Ethnology and Folkloristics)
This paper aims to investigate the relevance of metaphor and metonymy to ancient dream interpretation in Islamic-Iranian culture. To this end, a most-referenced book of dream interpretation is analysed according to the conceptual metaphor theory. The results show that metaphor and metonymy play an important role in this ancient discourse. The metaphorical dream is based either on a resemblance between the dream as the source domain and its interpretation as the target domain, or on some symbolic metaphors arising from cultural conventions. The metonymic dream is formed by a contiguous relationship between the dream as the vehicle entity and its interpretation as the target entity. Concerning metaphorical dream interpretation, it can be argued that the overt content of the dream is mapped onto the latent content by resemblance or cultural convention. As regards metonymic dream interpretation, it can be said that the overt content of the dream is mapped onto the latent content by a conceptual metonymy based on socio-physical context. In addition, there are two other procedures of dream interpretation based on realistic representation and the technique of reversion. These cases do not apply figurative devices like metaphor and metonymy. Also, the dreamer’s personal knowledge of his or her life does not play a significant role in the discourse of dream interpretation in Islamic-Iranian culture.